Retrieval of displaced dental implant in maxillary sinus by modified Caldwell Luc technique - Bhuse, Kruttika; Chaubal, Tanay V.; Bapat, Ranjeet (South African Dental Journal, 2023)
Displacement of dental implants into the maxillary sinus is an uncommon complication during implant placement. Here we present a case report of retrieval of dental implant displaced in the maxillary sinus with modification of Caldwell-Luc technique. A 35-year-old man presented to our institution for replacement of the maxillary right first molar using dental implant. At the point of final tightening of the implant, it suddenly got displaced into the maxillary sinus. The displaced dental implant was retrieved by performing a modification of the Caldwell-Luc technique which utilises gravitational force, saline as a vehicle and a tight-fitting suction tip in the surgically created lateral window. He was also instructed in coughing and sneezing techniques. Medical and dental professionals can utilise this technique effectively when advanced equipment such as endoscopes are not available to retrieve dental implants displaced in the maxillary sinus and it also preserves significant amount of alveolar bone in comparison to the traditional Caldwell Luc technique